Hello friends,

Welcome to my article How to solve x+1 x-1 + x-2 x+2 =4- 2x+3 x-2 ;x ne1,-2,2 ?

This article has been taken from the simplification lesson, in this article we have been told to simplify with the action of addition, subtraction, multiplication, division and fractions.

For complete information on how to solve this x+1 x-1 + x-2 x+2 =4- 2x+3 x-2 ;x ne1,-2,2 , read and understand it carefully.

Let us read / understand about this article x+1 x-1 + x-2 x+2 =4- 2x+3 x-2 ;x ne1,-2,2

First of all we should write the article on the page of the notebook.

## x+1 x-1 + x-2 x+2 =4- 2x+3 x-2 ;x ne1,-2,2 ?

We should use these methods while solving this type of question,

Let’s solve it by placing it up and down,

While solving these types of questions, we find the LCM of the denominator of their terms.

Then after that solve like this.

Then multiply these terms diagonally.

In doing so,

\displaystyle (2{{x}^{2}}+4)(x+2)=(2x-11)({{x}^{2}}+x-2) \displaystyle 2x.{{x}^{2}}-4{{x}^{2}}+4x-8=2x.{{x}^{2}}+2{{x}^{2}}-4x-11{{x}^{2}}-11x+22 \displaystyle 2x.{{x}^{2}}-2x.{{x}^{2}}-4{{x}^{2}}-2{{x}^{2}}+11{{x}^{2}}+4x+4x+11x-8-22=0 \displaystyle -6{{x}^{2}}+11{{x}^{2}}+8x+11x-8-22=0 \displaystyle 5{{x}^{2}}+19x-8-22=0 \displaystyle 5{{x}^{2}}+19x-30=0 \displaystyle 5{{x}^{2}}+25x-6x-30=0 \displaystyle 5x(x+5)-6(x+5)=0 \displaystyle (x+5)(5x-6)=0If

x +5=0

So ,

x =-5 Answer

If ,

5x -6 = 0

So,

x =6/5 Answer

** x+1 x-1 + x-2 x+2 =4- 2x+3 x-2 ;x ne1,-2,2 **?This article has been completely solved by tireless effort from our side, still if any error remains in it then definitely write us your opinion in the comment box. If you like or understand the methods of solving all the questions in this article, then send it to your friends who are in need.

Note: If you have any such question, then definitely send it by writing in our comment box to get the answer.

Your question will be answered from our side.

Thank you once again from our side for reading or understanding this article completely.